Transport and structural properties of MgB2/Fe wires produced by redesigning internal Mg diffusion process. (1st April 2022) - Yetiş, Hakan; Avcı, Doğan; Karaboğa, Fırat; Aksoy, Canan; Gajda, Daniel; Martínez, Elena; Tanyıldızı, Fatih Mehmet; Zaleski, Andrzej; Babij, Michal; Tran, Lan Maria; Angurel, Luis Alberto; de la Fuente, G F; et al.
Abstract: We report transport, electromechanical, and structural properties of single core MgB2 /Fe wire produced using a new fabrication method, called designed internal Mg diffusion (IMD) process, which relies on the use of non-stoichiometric Mg + B pellets with excess Mg in place of a central Mg rod used in the standard IMD method. Structural analysis revealed the successful formation of a porous MgB2 structure in the center and a dense circular MgB2 layer surrounding this structure in the designed-IMD wire. Fast transport I – V measurements showed that the designed IMD method increased engineering critical current density ( J e ) up to twice that of the IMD wires in self-field. The central porous MgB2 structure shared the applied current and indirectly behaved as an internal stabilizer against quench damage at high applied currents.